Protection of rice against Nilaparvata lugens by direct toxicity of sodium selenate. Issue 3 (8th November 2019) - Scheys, Freja; De Schutter, Kristof; Subramanyam, Kondeti; Van Damme, Els J. M.; Smagghe, Guy
Abstract: Nilaparvata lugens is one of the most notorious pest insects of cultured rice, and outbreaks of N. lugens cause high economic losses each year. While pest control by chemical pesticides is still the standard procedure for treating N. lugens infections, excessive use of these insecticides has led to the emergence of resistant strains and high pesticide residues in plants for human consumption and the environment. Therefore, novel and environment‐friendly pest control strategies are needed. In previous studies, selenium was shown to protect selenium‐accumulating plants from biotic stress. However, studies on nonaccumulator (crop) plants are lacking. In this study, rice plants ( Oryza sativa, Nipponbare) were treated with sodium selenate by seed priming and foliar spray and then infested with N. lugens . Brown planthoppers feeding on these plants showed increased mortality compared to those feeding on control plants. Treatment of the plants with sodium selenate did not affect the enzymes involved in the biosynthesis of the plant stress hormones jasmonic acid and salicylic acid, suggesting that the observed insect mortality cannot be attributed to the activation of these hormonal plant defenses. Feeding assays using an artificial diet supplemented with sodium selenate revealed direct toxicity toward N. lugens . With a low concentration of 6.5 ± 1.5 µM sodium selenate, half of the insects were killed after 3 days. In summary, sodium selenate treatment of plants can be used as a potential alternative pest management strategy to protect rice against N. lugens infestation through direct toxicity. Abstract : Treatment of rice plants with sodium selenate by seed priming and foliar spray causes increased mortality of Nilaparvata lugens . Sodium selenate revealed a direct toxic effect to the aphid when supplemented to the artificial diet. Highlight: The effect of sodium selenate treatment against insect infestations on non‐accumulator plants was analyzed. BPH feeding on Na2 SeO4 treated rice plants showed increased mortality. Feeding assays revealed a direct toxic effect of Na2 SeO4 to BPH.